Political personalizing: the politician’s image as electoral strategy - Orejuela Seminario, Sandra (2022)
In the last decades, academic research strongly poses again that image to a politician is of up most importance, specifically in vote obtaining campaigns. The predominance of the candidate’s image in the political message is a direct effect of the professionalizing of electoral campaigns and it is regarded as personalizing of politics. The following article explains how personal image is managed in the electoral communication process and states that personalizing, even when it simplifies the political debate, has also shown to facilitate it. The key through which simplification of the message does not lead it to its triviality can be found in the proper suitability between the image projected and the personal image which supports it. When a politician can support, through his own biography and personal qualities, a government project, it adds a guarantee to improve not only political dialogue, but political acting itself.